Metabolic effects of vasopressin in pathophysiology of diabetic kidney disease - Lebedeva, Svetlana; Margaryan, Arus; Smolyarchuk, Elena; Nedorubov, Andrey; Materenchuk, Maria; Tonevitsky, Alexander; Mutig, Kerim (Frontiers in Endocrinology, 2023)
The diabetic kidney disease (DKD) is the major cause of the chronic kidney disease (CKD).Enhanced plasma vasopressin (VP) levels have been associated with the pathophysiology of DKD and CKD. Stimulation of VP release in DKD is caused by glucose-dependent reset of the osmostat leading to secondary pathophysiologic effects mediated by distinct VP receptor types.VP is a stress hormone exhibiting the antidiuretic action in the kidney along with broad adaptive effects in other organs. Excessive activation of the vasopressin type 2 receptor (V2R) in the kidney leads to glomerular hyperfiltration and nephron loss, whereas stimulation of vasopressin V1a or V1b receptors in the liver, pancreas, and adrenal glands promotes catabolic metabolism for energy mobilization, enhancing glucose production and aggravating DKD. Increasing availability of selective VP receptor antagonists opens new therapeutic windows separating the renal and extra-renal VP effects for the concrete applications. Improved understanding of these paradigms is mandatory for further drug design and translational implementation. The present concise review focuses on metabolic effects of VP affecting DKD pathophysiology.